Prince-Patriarch Vajirañāṇavarorasa: The Dynamics of Adapting the Format of Techniques for Presenting the Buddhadhamma to the General Populace - Phosrikham, Phramahasarawut (Journal of Dhamma for Life, 2025)
This study aims to investigate the dynamic strategies employed by Prince-Patriarch Vajirañāṇavarorasa in the dissemination of Buddhist teachings and to develop a framework for adapting these methods to the digital age context. The research adopts a qualitative methodology, integrating textual analysis of primary source materials authored by Prince-Patriarch Vajirañāṇavarorasa with in-depth interviews conducted with subject matter experts in Buddhism, communication, and contemporary religious studies. This dual approach facilitates a comprehensive understanding of both the original doctrinal intent and its applicability in modern contexts. Findings indicate that Prince-Patriarch Vajirañāṇavarorasa a played a pivotal role in reforming and systematizing the propagation of Dhamma through five core dynamic strategies: (1) the articulation of Buddhist teachings in simplified, accessible language; (2) the institutionalization of structured religious education; (3) the strategic utilization of print media to broaden public engagement; (4) the reorganization of monastic governance through legal and administrative reforms; and (5) the integration of Buddhist principles with contemporary academic disciplines. In terms of contemporary relevance, the research reveals that these traditional methods have been meaningfully extended into digital platforms, including the website mahasamana.org, the Facebook page “Vajirananavarorasa Vidyā,” and the Instagram account “Vajirananavarorasa_vidaya.” These adaptations demonstrate a capacity for temporal responsiveness without compromising the doctrinal essence, offering a viable model for the sustainable communication of Buddhist teachings in the digital era.